Phase I and pharmacokinetic study of lonafarnib, SCH 66336, using a 2-week on, 2-week off schedule in patients with advanced solid tumors - Castaneda, Carlos (2011)
Purpose: This phase I study was performed to determine the safety profile, maximum tolerated dose (MTD) and biological activity of lonafarnib (SCH 66336). Single-dose and multi-dose pharmacokinetics were conducted. Methods: Twenty-one patients with advanced solid tumors were enrolled. Each patient received single-dose administration on day 1, cycle 1 then switched to a twice daily (BID) dosing regimen on days 2-14 of a 28-day cycle; subsequent cycles continued BID dosing on days 1-14. Dose-limiting toxicity (DLT) was assessed during the cycle one; toxicity evaluation was closely monitored throughout the treatment. Radiographic scans were completed to assess tumor response. Blood and urine pharmacokinetics were evaluated on days 1 and 14 in cycle 1. SCH 66336- induced farnesylation inhibition was assessed via conversion of prelamin A to lamin in buccal mucosa. Results: DLT and most common adverse events were diarrhea, fatigue, nausea and anorexia. No grade 3 or 4 hematological toxicities were observed. Nineteen of 21 patients were evaluable for response; short-term stable disease was observed in 5 patients. SCH 66336 systemic exposure increased with dose; however, drug accumulation was higher than projected. Renal excretion of parent drug was negligible. Farnesyl transferase inhibition was detected at the 200 and 300 mg BID doses. Conclusion: The MTD and recommended phase II dose is 200 mg BID on days 1-14 of a 28-day dosing regimen. The plasma concentration profile suggests the pharmacokinetics of SCH 66336 is dose and time dependent. Farnesyl transferase target inhibition was observed at doses of lonafarnib recommended for further study.